Obstructive sleep apnea syndrome in children - Brzecka, Anna; Teplicki, Andrzej (Przewodnik Lekarza/Guide for GPs, 2010)
Recently, there has been a marked increase in the recognition sleep related breathing disorders in children, including obstructive sleep apnea (OSA) syndrome. OSA syndrome is caused by intermittent partial or complete upper airway occlusion during sleep leading to sleep hypoxemia and sleep disturbances. It may be associated with the neurobehavioral and cardiovascular morbidities. Overnight polysomnography remains the gold standard test enabling the diagnosis of mild, moderate and severe pediatric OSA syndrome. Adenotonsillectomy is the treatment of choice for the majority of children with OSA syndrome.